Evaluate the Rate of Pollution in Soil using Simulink Environment - Mohammed Tawfiq, Luma Naji; Hasan, Mohammed A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
In this paper we design a Simulink model which can be evaluate the concentration of Copper, Lead, Zinc, Cadmium, Cobalt, Nickel, Crum and Iron. So, this model would be a method to determine the contamination levels of these metals with the potential for this contamination sources with their impact. The aim of using Simulink environment is to solve differential equations individually and as given data in parallel with analytical mathematics trends. In general, mathematical models of the spread heavy metals in soil are modeled and solve to predict the behavior of the system under different conditions.